2016
DOI: 10.1093/jee/tow112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an Action Threshold-Based Insecticide Program on Onion Cultivars Varying in Resistance to Onion Thrips (Thysanoptera: Thripidae)

Abstract: Onion thrips, Thrips tabaci Lindeman (Thysanoptera: Thripidae), is a highly destructive pest of onion, Allium cepa L., and its management relies on multiple applications of foliar insecticides. Development of insecticide resistance is common in T. tabaci populations, and new strategies are needed to relax existing levels of insecticide use, but still provide protection against T. tabaci without compromising marketable onion yield. An action threshold-based insecticide program combined with or without a thrips-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…Onion thrips populations also have been shown to develop resistance to insecticides in New York, USA (Shelton et al, 2003), Canada (MacIntyre Allen et al, 2005), and New Zealand (Martin et al, 2003). Although insecticides continue to be relied upon for onion thrips control, efforts to reduce insecticide use have been encouraged through the adoption of action thresholds and thrips-resistant cultivars (Nault & Huseth, 2016;Leach et al, 2017). In New York, onion growers have substantially increased their adoption of action thresholds and rotation of insecticide classes with the primary goal of mitigating insecticide resistance development in onion thrips populations (Leach et al, 2018b).…”
Section: Potato and Onion Farming As Prime Examples Of Highinput Intementioning
confidence: 99%
“…Onion thrips populations also have been shown to develop resistance to insecticides in New York, USA (Shelton et al, 2003), Canada (MacIntyre Allen et al, 2005), and New Zealand (Martin et al, 2003). Although insecticides continue to be relied upon for onion thrips control, efforts to reduce insecticide use have been encouraged through the adoption of action thresholds and thrips-resistant cultivars (Nault & Huseth, 2016;Leach et al, 2017). In New York, onion growers have substantially increased their adoption of action thresholds and rotation of insecticide classes with the primary goal of mitigating insecticide resistance development in onion thrips populations (Leach et al, 2018b).…”
Section: Potato and Onion Farming As Prime Examples Of Highinput Intementioning
confidence: 99%
“…Onion thrips has developed resistance to pyrethroids, organophosphates, and carbamates . Previous research has identified two pest management practices that should mitigate insecticide resistance and control onion thrips populations; using an action threshold and following an insecticide sequence that rotates insecticide classes . The use of thresholds is an important component to insecticide resistance management programs .…”
Section: Introductionmentioning
confidence: 99%
“…The use of thresholds is an important component to insecticide resistance management programs . In onion production in the Great Lakes region, an action threshold of one thrips per leaf has been effective in controlling thrips populations without reducing yield . Implementing an action threshold to control thrips in onion production can reduce the frequency of insecticide applications between 30% and 50%, thereby reducing exposure of insecticides to onion thrips populations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrips tabaci infestations in onion are typically managed using multiple applications of insecticides (Gill et al. ), and the recent development of action thresholds encourages fields to be sampled weekly to determine control decisions (Nault and Shelton ; Nault and Huseth ). Currently, a decision to control T. tabaci is based on sampling only a few onion fields on the entire farm.…”
Section: Introductionmentioning
confidence: 99%